Deaths in cots are not always cot deaths. Issue 2 (February 1985) - Sunderland, R
Abstract : Agonal histories were traced for 1182 of 1782 postneonatal deaths in Sheffield between 1947 and 1979. Twenty eight per cent of these deaths were histologically inexplicable, 19% were from infections and 15% from malformations. These sudden infection and malformation deaths were explicable, yet by some definitions they would be considered as cot deaths. Varying definitions may lead to confusion, hindering the search for aetiological mechanisms.